2000
DOI: 10.1111/j.1540-8191.2000.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Parsonnet Risk Scale Identifies Limits to Early Patient Discharge

Abstract: A simplified Parsonnet risk scale (three categories) is an effective tool in identifying factors limiting fast-track recovery. Low- and intermediate-risk patients represent the majority (82%) and respond well to fast-track methods. High-risk patients (18%) are limited by a greater percentage of female patients, reoperative CABG, and the very elderly, resulting in fast-track failure. Strategies to improve recovery in high-risk patients may include evolving off-pump techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Our data indicate that a longer course of care is needed for functional recovery in this patient population. These findings are consistent with the results of previous research showing that older patients who undergo cardiac surgery have longer lengths of stay (Horneffer et al, 1987; Ott et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that a longer course of care is needed for functional recovery in this patient population. These findings are consistent with the results of previous research showing that older patients who undergo cardiac surgery have longer lengths of stay (Horneffer et al, 1987; Ott et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…While there is some evidence that accelerated discharge programs are safe for elderly patients (Lee, Swain, Andrey, Murrell, & Geha, 1999; London et al, 1997; Ott, Gutfinger, Miller, Alimadadian, & Tanner, 1997), others have demonstrated that older patients have a significantly higher acuity of illness (Kurki, Hakkinen, Lauharanta, Ramo, & Leijala, 2001) and are twice as likely to develop postoperative atrial fibrillation as younger patients (Aranki et al, 1996; Mathew et al, 1996). To add to the controversy, multiple investigators have found age to be an independent risk factor for extended PLOS after coronary artery bypass graft (CABG) surgery (Horneffer et al, 1987; Kurki et al, 2001; Ott et al, 2000).…”
mentioning
confidence: 99%